Variability of agronomic characters related to resistance to stem canker (Phytophthora palmivora) on duku (Lansium domesticum) along Batanghari River, Sumatra, Indonesia - ISLAH HAYATI; SURYO WIYONO; WIDODO WIDODO; SOBIR SOBIR (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Hayati I, Wiyono S, Widodo, Sobir. 2019. Variability of agronomic characters related to resistance to stem canker (Phytophthora palmivora) on duku (Lansium domesticum) along Batanghari River, Sumatra, Indonesia. Biodiversitas 20: 1127-1132. Duku (Lansium domesticum Correa) is a tropical favorite fruit in South East Asia, including Indonesia. However, currently stem canker disease caused by Phytophthora palmivora Butler (Butler) has been a serious problem on duku plant in Indonesia, especially in Jambi Province. Since duku is vegetatively propagated, selecting resistant mother trees is an effective approach to overcome the disease. This research was aimed to identify mother trees and their progenies that resistant to stem canker pathogen. The research was conducted in two stages. The first one was morphological identification of healthy-looked mother trees grown at four locations: three in Batanghari and one in Muaro Jambi District. The second stage was analyzing resistant seedling progeny of mother trees identified at the first stage. At the second stage, 3 month old seedlings were inoculated with P. palmivora, isolated from rhizosphere of trees grown at the researchs location using Completely Randomized Design. The research found 19 healthy mother trees, and showed similarity index of 0.40 based on eleven identified agronomic characters of mother trees. Cluster analysis revealed 2 identified clusters of mother trees with the identified clusters were independent of plant growth locations. Seedling resistant analysis showed that there were only 5 seedlings expressing resistant traits. Correlation analysis showed that the resistant seedlings were originated from mother trees which tend to have longer leaves, more fruits per branch, more yields, and bigger canopies. This information of the characters can possibly become future reference to choose resistant plant as sources of mother trees to develop and maintain duku populations along the Batanghari River.